Measuring privatization: comparing five indicators of the disposition of state-owned enterprises in advanced democracies - Son, Keonhi; Zohlnhöfer, Reimut (Journal of comparative policy analysis, 2019)
While numerous indicators have been suggested in the scholarly literature on the determinants of privatization, they have mostly been treated as equivalents without much attention to how closely they are matched. This paper compares five prominent operationalizations of privatization. It finds that correlations between these indicators are worryingly low. Moreover, it shows that results of otherwise identical regressions differ immensely depending on which indicator of privatization is used. As a way forward, seeing the various indicators not as equivalents but as measuring different aspects of the phenomenon under study is suggested.